PERAN MAHASISWA KKN DALAM MENUMBUHKAN KESADARAN LINGKUNGAN MELALUI AKSI BEACH CLEAN UP DI DESTINASI WISATA PULOMERAK KECIL - Afriani, Raden Irna; Rustandi, Tata; Firmansyah , Adrian Azril; Anjelena , Reni; Sefyanti , Hanna; Nadiputri, Adzra Qonita (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
Environmental pollution in coastal areas, particularly due to inorganic waste such as plastic, poses a serious threat to ecosystems and tourism aesthetics. In response, students of Universitas Bina Bangsa carried out a Beach Clean Up program at Pulomerak Kecil Beach, Cilegon City, as part of their community service project (KKN). This activity aimed to raise awareness among local residents and visitors about the importance of coastal cleanliness through direct action and environmental education. Using a descriptive qualitative method, the program involved cleaning the shoreline, installing educational banners, and conducting outreach on the impacts of pollution. The initiative successfully engaged students, youth groups, and local communities, fostering social solidarity and a culture of environmental care. The results demonstrate that participatory and educational approaches are effective in promoting sustainable environmental practices in tourist areas.